Prevalence and Positive Correlates of Posttraumatic Stress Disorder Symptoms among Chinese Patients with Hematological Malignancies: A Cross-Sectional Study. - Li Liu; Yi-Long Yang; Zi-Yue Wang; Hui Wu; Yang Wang; Lie Wang (PLoS ONE)
Purpose Positive psychological constructs have been given increasing attention in research on the coping resources of cancer-related distresses. However, little research is available on posttraumatic stress disorder (PTSD) in patients with hematological malignancies. The purposes of this study were to assess the prevalence of PTSD symptoms and to explore the associations of perceived social support (PSS), hope, optimism and resilience with PTSD symptoms among Chinese patients with hematological malignancies. Methods A cross-sectional study was conducted during the period from July 2013 through April 2014. A total of 225 inpatients with hematological malignancies, which were eligible for the study, completed the Post-traumatic Stress Checklist-Civilian Version, Multidimensional Scale of Perceived Social Support, Adult Hope Scale, Life Orientation Scale-Revised, and Resilience Scale. Hierarchical regression analysis was performed to explore the correlates of PTSD symptoms. Results Overall, the prevalence of PTSD symptoms was 10.7%. Initially, PSS was negatively associated with PTSD symptoms (β = -0.248, P < 0.01). However, when positive psychological variables were added, optimism was negatively associated with PTSD symptoms (β = -0.452, P < 0.01), and gender had a significant effect on PTSD symptoms. Women were more vulnerable to these symptoms than men (β = 0.123, P < 0.05). When the analysis was performed separately by gender, only optimism showed a significantly negative association with PTSD symptoms in both men (β = -0.389, P < 0.01) and women (β = -0.493, P < 0.01). Conclusions Some patients with hematological malignancies suffer from PTSD symptoms. The positive effects of PSS and optimism on PTSD symptoms suggest that an integrated approach to psychosocial intervention from both external and internal perspectives could have practical significance. Gender difference should be considered in developing potential interventions in reducing cancer-related PTSD symptoms.